2019
DOI: 10.1259/dmfr.20190053
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex estimation based on pulp cavity volume using cone beam computed tomography: development and validation of formulas in a Brazilian sample

Abstract: Objectives: To develop and validate formulas for age and sex estimation based on the pulp cavity volume of teeth using cone beam CT. Methods: The sample was composed of 116 cone beam CT scans from Brazilian individuals of both sexes, ranging in age from 13 to 70 years. A total of 232 teeth (upper central incisors and canines) were evaluated. Two calibrated examiners determined pulp cavity volumes using the ITK-SNAP software. Pearson’s correlation test was used to assess the correlation between chronological ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…Indeed, 36.6% of the age variability was explained by the pulp chamber/crown volume ratio for upper incisors, and the differences between chronological and estimated age was <5 years for 31.3% of these teeth. Similar results have been published by other authors, indicating that the pulp tooth volume ratio of incisors offers a reliable DAE method [3,8,13,16,[26][27][28]. However, results for canines did not prove to be a reliable approach to age estimation in this Spanish population, unlike findings in Malaysian [8], Tunisian [23], Iranian [28], Indian [12], and Pakistani [32] populations.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Indeed, 36.6% of the age variability was explained by the pulp chamber/crown volume ratio for upper incisors, and the differences between chronological and estimated age was <5 years for 31.3% of these teeth. Similar results have been published by other authors, indicating that the pulp tooth volume ratio of incisors offers a reliable DAE method [3,8,13,16,[26][27][28]. However, results for canines did not prove to be a reliable approach to age estimation in this Spanish population, unlike findings in Malaysian [8], Tunisian [23], Iranian [28], Indian [12], and Pakistani [32] populations.…”
Section: Discussionsupporting
confidence: 85%
“…The progressive decrease of pulp volume over time has been used to estimate dental age in adult individuals [3,8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], although the apposition of secondary dentine is not homogeneous on all walls of the pulp cavity [21]. Difficulties have been reported in detecting minute structural demarcations at the root apex (pulp tissue and calcified tooth structures) and undertaking this manually for this purpose would be time-consuming [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental setup. Regarding the validation method for age prediction in forensic anthropology, Andrea et al [37] discussed common issues that were encountered when using incorrect procedures. Several reported studies did not validate over unseen data, which could lead to an overfitting problem.…”
Section: Plos Onementioning
confidence: 99%
“…Similarly, another study in the Malaysian population also revealed higher errors of age prediction from the pulp volume of maxillary canines in the age group of 46-65 years old (Asif et al 2019). In the Brazilian population, Andrade et al (2019) demonstrated high accuracy of age estimation from the upper incisors and canines in individuals older than 35 years. This finding could be attributed to the consistent dentine deposition which occurs at regular intervals in the middle age; however, this deposition is rapid both in younger ages until 30 years old and again in the older age groups (Kazmi et al 2019).…”
Section: Discussionmentioning
confidence: 93%